Dynamic response of the Martian ionosphere to an interplanetary shock: Mars Express and MAVEN observations. Issue 18 (18th September 2017) - Harada, Y.; Gurnett, D. A.; Kopf, A. J.; Halekas, J. S.; Ruhunusiri, S.; Lee, C. O.; Hara, T.; Espley, J.; DiBraccio, G. A.; Mitchell, D. L.; Mazelle, C.; Larson, D. E.; et al.
Abstract: Multipoint observations from the Mars Advanced Radar for Subsurface and Ionosphere Sounding (MARSIS) instrument on board Mars Express and the Mars Atmosphere and Volatile EvolutioN (MAVEN) mission reveal a dynamic response of the Martian ionosphere to abrupt variations in the upstream solar wind plasma. On 2 February 2017, MAVEN, located upstream from the Martian bow shock, encountered a corotating interaction region‐related interplanetary shock with a sudden enhancement in the dynamic pressure. MARSIS, operating in the upper ionosphere at ∼478 km altitudes and ∼78° solar zenith angles, observed a sharp increase in the local magnetic field magnitude ∼1 min after the shock passage at MAVEN. The time lag is roughly consistent with the expected propagation time of a pressure pulse from the bow shock to the upper ionosphere at the fast magnetosonic speed. Subsequently, remote soundings recorded disturbed signatures of the topside ionosphere below Mars Express. Key Points: Simultaneous MEX and MAVEN observations demonstrate that the Martian ionosphere responds quickly to an interplanetary shock passage The response time is consistent with propagation of a pressure pulse from the bow shock to the ionosphere in the fast magnetosonic mode Remote soundings reveal the presence of irregular structures in the topside ionosphere shortly after the shock passage